2021
DOI: 10.1210/clinem/dgab429
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-Pituitary Autoimmunity and Related Impairment of Hormone Secretions in Chronic Fatigue Syndrome

Abstract: Context Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a severe chronic illness which reduces the quality of life. A potential role of neuroendocrine autoimmune dysfunction has been hypothesized. Objective To investigate the occurrence of anti-pituitary (APA) and anti-hypothalamic (AHA) antibodies and possible related hypothalamic/pituitary dysfunctions in ME/CSF patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…This proposal is consistent with descriptions of ME/CFS as a progression from a hypermetabolic to hypometabolic state (21). It also aligns with a recent hypothesis relating many of the symptoms in severe ME/CFS to impaired pituitary function (111). Further support for this proposal is provided by the many previous ME/CFS studies that have documented dysfunctions in the hypothalamic-pituitary-somatotropic (HPS) axis (112)(113)(114), the HPT axis (115)(116)(117)(118)(119)(120), and the HPA axis (121-136)-notably associated with inflammation and oxidative & nitrosative stress (O&NS) (137)(138)(139)(140).…”
Section: Pituitary Suppressionsupporting
confidence: 90%
See 1 more Smart Citation
“…This proposal is consistent with descriptions of ME/CFS as a progression from a hypermetabolic to hypometabolic state (21). It also aligns with a recent hypothesis relating many of the symptoms in severe ME/CFS to impaired pituitary function (111). Further support for this proposal is provided by the many previous ME/CFS studies that have documented dysfunctions in the hypothalamic-pituitary-somatotropic (HPS) axis (112)(113)(114), the HPT axis (115)(116)(117)(118)(119)(120), and the HPA axis (121-136)-notably associated with inflammation and oxidative & nitrosative stress (O&NS) (137)(138)(139)(140).…”
Section: Pituitary Suppressionsupporting
confidence: 90%
“…Similarly, the administration of ghrelin to the I/R rats “inhibited pro-inflammatory cytokine release, reduced neutrophil infiltration, ameliorated intestinal barrier dysfunction, attenuated organ injury, and improved survival” ( 200 ). The sequence between intestinal injury, ghrelin secretion and GH release by the pituitary could be particularly relevant for solving ME/CFS given that “several of the main typical symptoms in severe ME/CFS, such as fatigue, myalgia, contractility, delaying muscle recovery and function, exertional malaise, neurocognitive dysfunction, and physical disability may be related to severe GH deficiency” ( 111 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on Korean patients with the HBV reported that patients with higher fatigue levels had lower levels of cortisol [ 16 ]. This pattern of cortisol is similar to that of chronic fatigue syndrome [ 39 ]. To better assess the effects of the Hep B Care ® program on fatigue as one of the major symptoms in individuals with the HBV, further studies will need to be conducted with objective outcome indicators using a wider range of biomarkers.…”
Section: Discussionsupporting
confidence: 70%
“…None of the controls indicated an APA- or AHA-positive result. This study concluded that COVID-19 may cause secondary or tertiary adrenal insufficiency and that pituitary/ hypothalamic autoimmunity may play a role in this dysfunction; thus, a routine screening of adrenal function, as well as AHA and APA evaluations in these patients, should be recommended [ 30 , 31 , 32 ]. Considering these results, even if studies on the pituitary involvement in acute phase of this infection are scarce, a sequela of pituitary dysfunction, especially linked to pituitary autoimmunity in patients hospitalized from the acute phase of this infectious disease, could not be excluded.…”
Section: Hypothalamic-pituitary Autoimmunity In Sars-cov-2 Infectionmentioning
confidence: 99%